Reproduction and Sexual Maturity of European Sardine (Sardina pilchardus) in the Central Mediterranean Sea - Basilone, Gualtiero; Ferreri, Rosalia; Aronica, Salvatore; Mazzola, Salvatore; Bonanno, Angelo; Gargano, Antonella; Pulizzi, Maurizio; Fontana, Ignazio; Giacalone, Giovanni; Calandrino, Pietro; Genovese, Simona; Barra, Marco (Frontiers in Marine Science, 2021)
Understanding drivers of fish maturity is essential to predict the productivity, stability, and resiliency of exploited populations. Size at maturity for European sardine (Sardina pilchardus) in the Central Mediterranean Sea has never been published within rigorous peer review process. In the past, stock assessment working groups in the Mediterranean requested such information; however, the size at which 50% of the fish population reaches the sexual maturity (L50) often received weak estimates based on a single or few years of observation, which do not necessarily reflect the whole stock. To address this data gap for the Central Mediterranean Sea, the present research estimated size at maturity of European sardine in the Strait of Sicily. In the study period (2009-2017), collected individuals exhibited significant differences in size range as well as in body condition and reproductive effort. Data also permitted a clear identification of the spawning season, starting in September-October and ending in March-April nthe following year. Along the analysed period, the size at first maturity ranged from 108 mm to 124 mm (total length) for females and from 102 mm to 122 mm for males. Significant differences were recorded among sexes and years. Moreover, a goodness-of-fit measure was proposed to assess the robustness and reliability of L50 estimates, and thus selecting those that minimize the fitting associated errors. Finally, results suggested that the low proportion of immature individuals in the samples represents the main source of bias in L50 estimation and possible solution was also proposed.